Hydrogen-Bonding Recognition-Induced Colorimetric Determination of Hydrazine Based on the Tryptophan Capped Gold Nanoparticles - Wenhua Gao; Jing Xi; Yunsheng Chen; Song Xiao; Xingqing Wang; Jun Li; Jincheng Xiao; Yaowen Chen (Journal of Spectroscopy)
A simple, cost-effective, and rapid colorimetric method for hydrazine detection using tryptophan-caped gold nanoparticles (Trp-AuNPs) has been developed. Tryptophan (Trp) is a protein with reducibility and amino group which can reduce chloroauric acid (HAuCl4) to AuNPs and modify the surface of AuNPs simultaneously. The Trp-AuNPs could be used to quantitatively detect hydrazine and showed different responses to vary concentration of hydrazine in an aqueous solution based on the aggregation-induced color change of Trp-AuNPs. The real water sample analysis verified the conclusion. The sensitivity of the detection system was influenced by the size of AuNPs which is determined by the pH of the detection system, the concentration of Trp, and the react time. We found that higher temperature contributed to more rapidly results. The detection system can detect as low as 1 μM hydrazine. We expect our approach to have wide-ranging applications in the developing region for monitoring water quality in some areas.